Factors influencing the nutritional status of children aged 6–23 months based on the Composite Index of Anthropometric Failure (CIAF) - Rizki Maulidya; Zulfan Zulfan; Sarah Nadya; Amelia Zahara (AcTion: Aceh Nutrition Journal, 2025)
Lhokseumawe City still experiences the nutritional problems of being underweight, stunting, and wasting, so it is necessary to know the factors that cause it, especially in the Banda Sakti Health Center. The aim of this study was to determine the factors that affect the nutritional status of children aged 6-23 months according to the Composite Index of Anthropometry (CIAF). This cross-sectional study was conducted at the Banda Sakti Health Center in 2023. A total of 314 children aged 6-23 months were randomly selected. Data were collected via interviews, questionnaires, and anthropometric measurements (weight and height). Nutritional status data were processed using WHO Anthro 2005 software. Data were analyzed using the chi-squared test and logistic regression analysis. Results: The prevalence of growth failure in children at Banda Sakti Health Center was 23,2%. The determinants of growth failure were ANC (p=0,000; OR=20,8), birth weight (p=0,000; OR=8,44), complementary feeding diversity (p=0,000; OR=10,3), animal protein consumption (p=0,000; OR=17,23), and complete immunization (p=0,000; OR=4,41). Antenatal Care (ANC) examination was the dominant factor affecting the incidence of growth failure in children aged 6-23 months (OR= 20,8). In conclusion, incomplete ANC examination is the dominant factor associated with the incidence of growth failure in children aged 6-23 months at the Banda Sakti Health Center, Lhokseumawe City.